Mussel-inspired multi-bioactive microsphere scaffolds for bone defect photothermal therapy - Kaixuan Ma; Lei Yang; Wenzhao Li; Kai Chen; Luoran Shang; Yushu Bai; Yuanjin Zhao (Materials Today Bio)
Hydrogel microspheres hold great promise as scaffolds for bone repair. Their hydrated matrix, biocompatibility, and functional properties make them an attractive choice in regenerative medicine. However, the irregularity of defect requires shape adaptability of the microspheres. Additionally, there is still room for improvement regarding the component of the microspheres to achieve sufficient bioactivity. Here, we prepare multi-bioactive microspheres composed of methacrylated silk fibroin (SFMA) via microfluidic electrospray. Magnesium ascorbyl phosphate (MAP) is encapsulated within the microspheres, whose sustained release facilitates angiogenesis and osteogenic differentiation. The microspheres are further coated with a polydopamine (PDA) layer, allowing them to assemble in situ into a scaffold that conforms to the non-uniform contours of bone defects. The photothermal conversion capability of PDA also provides mild photothermal stimulation to further promote bone regeneration. Based on the synergistic effects, our in vivo experiments demonstrated that the microsphere scaffold effectively promotes bone defect healing. Thus, this multi-bioactive scaffold offers a versatile strategy for bone repair with promising clinical potential.